Rebranding Madrasah dalam Membangun Citra Positif dan Modern - M. Yusuf (PT. Cahya Edupreneur Indonesia, 2023)
This article discusses rebranding in Islamic schools as a strategy to build a positive and modern image in society. Common issues faced by Islamic schools include negative perceptions and limited appeal to parents and prospective students. In the background, this article identifies the need for a change and transformation of the image to enhance the competitiveness and relevance of Islamic schools in an increasingly competitive educational landscape. The research method employed in this article is a literature review, involving the collection and analysis of various reference sources related to rebranding and marketing strategies in the context of Islamic education. The research objective is to provide practical guidance for Islamic schools in designing effective and successful rebranding initiatives. The results of this study indicate that key elements supporting the success of rebranding in Islamic schools include the development of relevant curricula, the integration of technology in teaching and learning, active community involvement, and appropriate communication approaches. By implementing effective rebranding, Islamic schools can create a positive and modern image, attract the interest of parents and prospective students, and enhance the overall quality of education.